MANAJEMEN PENDIDIKAN KARAKTER PESERTA DIDIK - Nunung Nurhasanah (Jurnal Tata Kelola Pendidikan, 2021)
This research is motivated by the existence of phenomena that occur in the moral and moral decline of adolescents in Indonesia. The management of character education for students is in a strategic position because the center of educational services is focused on students. Student character education needs to be planned thoroughly and systematically according to the needs of students. Researchers took the research focus as follows: (1) how the students’ coaching is planned, (2) how the students’ coaching is conducted, and (3) how the students’ coaching is evaluated at SMK Daarut Tauhiid Boarding School Bandung. The method used in this study is qualitative equipped with descriptive method. SMK Daarut Tauhiid Boarding School is here as an effort to realize the vision and mission of the Daarut Tauhiid Foundation to create experts in dhikr, thought and endeavors towards creation that has good character. The character education method used and adapted to the conditions of character education of students such as exemplary, habituation of BAKU character (Good and Strong), creation of climate and culture of Daarut Tauhiid and reward and punishment. Records of Islamic religious lessons and paying attention to basic scientific materials that support subjects that involve students and their educators can be relied on 24 hours a day and supported by a dormitory as a permanent residence for students. Control of students' character education is carried out effectively through teachers and musyrif/ah. It is carried out in several stages, namely one-week coordination evaluation, monthly meetings, final semester meetings and annual meetings conducted by the leadership together with teachers and musyrif / ah.